Hubungan Kualitas Tidur dengan Health-Related Quality of Life (HRQoL) pada Pegawai Universitas - Alip Abdurahman Nasir; Kuston Sultoni; Jajat (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to examine the relationship between sleep quality and Health-Related Quality of Life (HRQoL) among university employees. The method used was a quantitative study with an analytical observational approach and a cross-sectional design. A total of 77 university employees were recruited using a convenience sampling technique. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), while HRQoL was measured using the WHOQOL-BREF questionnaire. Data were analyzed using correlation tests to determine the relationship between the variables. The results showed that most respondents had poor sleep quality, and sleep quality was negatively associated with all HRQoL domains. A significant relationship was found in the psychological domain, indicating that poorer sleep quality was associated with lower psychological well-being. In conclusion, there is a relationship between sleep quality and Health-Related Quality of Life (HRQoL) among university employees, particularly in the psychological domain. Keywords: Health-Related Quality of Life, Sleep Quality, University Employees, Pittsburgh Sleep Quality Index, WHOQOL-BREF